1996
DOI: 10.1017/s0043174500094030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wetting/Drying Cycles on Dissipation Patterns of Bioavailable Imazaquin

Abstract: Greenhouse experiments determined differences in imazaquin bioavailability over time under various soil moisture regimes. All soils were initially fortified with 63 ppb (w/w) of commercially formulated imazaquin. Treatments consisted of maintaining at field capacity for 15 wk (FC), maintaining air-dry for 15 wk (AD), soil that was maintained air-dry for 2 wk and then wet to field capacity at 2 wk intervals (2WAD), and soil that was wet to field capacity at the initiation of the experiment and at 2 wk intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
(5 reference statements)
2
22
0
2
Order By: Relevance
“…Miles et al (1984) have also attributed the slower dissipation of chlorfenvinphos in dry soil as compared to moist soil, to lower microbial activity. Similar results have also been reported for 2,4-D (Johnson et al, 1995), imazaquin (Baughman and Shaw, 1996), chlorothalonil (Choudhury and Awasthi, 2000) and b-cyfluthrin (Gupta and Gajbhiye, 2002). However, such dry conditions are not likely to occur in fields under cropped conditions.…”
Section: Resultssupporting
confidence: 85%
“…Miles et al (1984) have also attributed the slower dissipation of chlorfenvinphos in dry soil as compared to moist soil, to lower microbial activity. Similar results have also been reported for 2,4-D (Johnson et al, 1995), imazaquin (Baughman and Shaw, 1996), chlorothalonil (Choudhury and Awasthi, 2000) and b-cyfluthrin (Gupta and Gajbhiye, 2002). However, such dry conditions are not likely to occur in fields under cropped conditions.…”
Section: Resultssupporting
confidence: 85%
“…2b). It has been suggested that soil moisture conditions affected the microbial activity on the degradation of pesticides in soil (Baughman & Shaw 1996; Karpouzas & Walker 2000). However, there was little difference in pethoxamid degradation in soil under different soil moisture conditions, although the reason for the difference in the rate of decrease of pethoxamid activity between the soil water and the soil solid phase has not been clarified yet.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that soil moisture affected the time‐course degradation of imidazolinone (Curran et al . 1992) and imazaquin (2‐[4,5‐dihydro‐4‐methyl‐4‐(1‐methylethyl)‐5‐oxo‐1 H ‐ imidazol‐2‐yl]‐3‐quinolinecarboxylic acid; Baughman & Shaw 1996). However, these reports have provided little information on the relationship between the residual phytotoxic activity and the behavior of soil‐applied herbicides under different moisture conditions in soil.…”
Section: Introductionmentioning
confidence: 99%
“…Weeds less susceptible to imazethapyr were not controlled satisfactorily in a sandy loam soil when there was no rain for 7–10 d after application, as no soil residual water was available to initiate herbicidal activity (Ayeni et al ., 1998). For imazaquin, a decrease in soil moisture would cause more herbicide to be sorbed and, as a result, would decrease bioavailability (Baughman & Shaw, 1996).…”
Section: Soil‐bound and Extracted Imazaquinmentioning
confidence: 99%